PERENCANAAN SISTEM PEMESANAN MAKANAN DI RUMAH MAKAN BERBASIS ONLINE MENGGUNAKAN MOBILE ANDROID DENGAN METODE BARCODE - Tulak, Monica Kristiani; Fiodinggo, Penidas (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The current development of information technology has affected various sectors of life, including the culinary sector. Modern restaurants and restaurants have switched to online-based food ordering systems. The purpose of this research is to design and develop a food ordering system at an online-based restaurant using an Android mobile with the barcode method. The barcode method is used to facilitate the food ordering process and assist users in making transactions quickly and efficiently. The results of system testing and validation show that an online-based food ordering system using an Android mobile with the barcode method can increase efficiency and effectiveness in the food ordering process. This research is expected to provide contributions and solutions for the culinary industry in utilizing information technology to improve service quality.